Hydrogen Sulfide (H2S) Signaling as a Protective Mechanism against Endogenous and Exogenous Neurotoxicants - Aschner, Michael; Skalny, Anatoly V.; Ke, Tao; da Rocha, Joao BT; Paoliello, Monica M.; Santamaria, Abel; Bornhorst, Julia; Rongzhu, Lu; Svistunov, Andrey A.; Djordevic, Aleksandra B.; Tinkov, Alexey A. (Current Neuropharmacology, 2022)
In view of the significant role of H2S in brain functioning, it is proposed that H2S may also possess protective effects against adverse effects of neurotoxicants. Therefore, the objective of the present review is to discuss the neuroprotective effects of H2S against toxicity of a wide spectrum of endogenous and exogenous agents involved in the pathogenesis of neurological diseases as etiological factors or key players in disease pathogenesis. Generally, the existing data demonstrate that H2S possesses neuroprotective effects upon exposure to endogenous (amyloid β, glucose, and advanced-glycation end-products, homocysteine, lipopolysaccharide, and ammonia) and exogenous (alcohol, formaldehyde, acrylonitrile, metals, 6-hydroxydopamine, as well as 1-methyl-4-phenyl- 1,2,3,6- tetrahydropyridine (MPTP) and its metabolite 1-methyl-4-phenyl pyridine ion (MPP)) neurotoxicants. On the one hand, neuroprotective effects are mediated by S-sulfhydration of key regulators of antioxidant (Sirt1, Nrf2) and inflammatory response (NF-ΚB), resulting in the modulation of the downstream signaling, such as SIRT1/TORC1/CREB/BDNF-TrkB, Nrf2/ARE/HO-1, or other pathways. On the other hand, H2S appears to possess a direct detoxicative effect by binding endogenous (ROS, AGEs, Aβ) and exogenous (MeHg) neurotoxicants, thus reducing their toxicity. Moreover, the alteration of H2S metabolism through the inhibition of H2S-synthetizing enzymes in the brain (CBS, 3-MST) may be considered a significant mechanism of neurotoxicity. Taken together, the existing data indicate that the modulation of cerebral H2S metabolism may be used as a neuroprotective strategy to counteract neurotoxicity of a wide spectrum of endogenous and exogenous neurotoxicants associated with neurodegeneration (Alzheimer’s and Parkinson’s disease), fetal alcohol syndrome, hepatic encephalopathy, environmental neurotoxicant exposure, etc. In this particular case, modulation of H2S-synthetizing enzymes or the use of H2S-releasing drugs should be considered as the potential tools, although the particular efficiency and safety of such interventions are to be addressed in further studies.
Keywords: neurotoxicants